Pengaruh Citra, Fasilitas, dan Kualitas Pelayanan Terhadap Keputusan Memilih SD Methodist - 11 - Veronika Leticia (Edukasia Jurnal Pendidikan, 2024)
This study aims to determine the effect of Image, Facilities, and Services Quality either partially or simultaneously on Decision to Choose Methodist – 11 primary school. This research uses descriptive and quantitative methods and data sources in the form of primary and secondary data. The population were all elementary school students at Methodist – 11 in 2021. The total sample was 199 students represented by their parents. The sampling technique used probability sampling with simple random sample. The data were analyzed using the multiple linear regression analysis method. The results showed that the image partially had a positive and significant effect on the Decision to Choose Methodist – 11 primary school. Facilities partially have no significant effect. Services quality has a positive and significant effect. Based on the results of simultaneous hypothesis testing, it is known that the results of the - F test show that the Image, Facilities, and Services Quality simultaneously affect the Decision to Choose Methodist – 11 primary school. The amount of adjusted R Square is 69.8%, which means that the remaining 30.2% is influenced by other factors.